Revalidation of the subgenus Dactylotergitius Verhoeff, and redescription of Otostigmus (D.) caudatus Brölemann and Otostigmus (D.) cavalcantii Bücherl (Scolopendromorpha: Scolopendridae: Otostigminae) - Chagas-Júnior, Amazonas; Knysak, Irene; Guizze, Samuel P.g. (Zootaxa, 2007)
The subgenus Dactylotergitius Verhoeff, 1937 of Otostigmus Porat, 1876 is revalidated, with Coxopleurotostigmus Bücherl, 1939 as its junior subjective synonym. Two species are recognized in Otostigmus (Dactylotergitius): Otostigmus (D.) caudatus Brölemann, 1902 and O. (D.) cavalcantii Bücherl, 1939, the latter with the following new synonyms: O. kretzii Bücherl, 1939, O. cavalacantii perdicensis Bücherl, 1943, O. sternosulcatus Bücherl, 1946, O. cavalcantii iberaensis Coscarón, 1955 and O. caudatus hogei Bücherl, 1974.